Faktor-Faktor yang Memengaruhi Penyerapan Tenaga Kerja Sektor Pertanian di Kabupaten Muaro Jambi - Lili Alfiati Tamala; Dompak Napitupulu; Ardhiyan Saputra (Program Studi Magister Agribisnis, Universitas Sebelas Maret, 2023)
This study aimed to analyze the factors that influence the absorption of labor in the agricultural sector in Muaro Jambi Regency. The method used is the multiple linear regression analysis methods. Based on the results of multiple linear regression tests, the independent variables in the form of GRDP in the agricultural sector, agricultural land area, UMR, and agricultural investment simultaneously significantly affect on employment in the agricultural sector in Muaro Jambi Regency. Then partially, the GRDP of the agricultural sector, the area of agricultural land, and agricultural investment have a positive and significant effect on employment in the agricultural sector. Meanwhile, the minimum wage variable negatively and significantly affects employment in the agricultural sector in Muaro Jambi Regency.